Influence of the second metal component on processing and selected properties of Al2O3-Cu hybrid composites - Piotrkiewicz Paulina; Zygmuntowicz Justyna; Wachowski Marcin; Szachogłuchowicz Ireneusz; Kaszuwara Waldemar (Processing and Application of Ceramics, 2024)
The aim of the work was to determine the influence of metallic phase content on the obtained properties of hybrid composites from the ceramics-metal system. Six series of samples from three systems (Al2O3-Cu, Al2O3- Cu-Ni and Al2O3-Cu-Cr) with two different contents of metallic phase (2.5 and 10 vol.%) were prepared by uniaxial pressing and pressure-less sintering. The research carried out in this work used the classic idea of material engineering, assuming the optimization of the material’s functional properties by shaping the microstructure in a suitably modified technological process. The possibility of producing composite samples with density exceeding 95%TD was confirmed. There was no significant effect of the composition and the share of the metallic phase on the obtained values. The microstructure observations showed that the addition of the second metallic component had a positive effect on the size of the metallic particles, limiting the formation of metal clusters of significant size visible in the case of Al2O3-Cu samples. Compressive strength tests have shown that the addition of the second component to the metallic phase has a positive effect on the compressive strength of the material.